Problemas procesales y de ejecución penitenciaria: justicia restaurativa y delitos socioeconómicos - Rebollo Vargas, Rafael (Estudios penales y criminologicos, 2021)
The present work, in the first place, the procedural difficulties that arise in the field of restorative justice and socioeconomic crimes are addressed. Thus, the viability of the private prosecution is examined, concluding that it is not the ideal mechanism to start the procedure since, in it, the procedural legitimacy is attributed to who is not offended or harmed, while in these crimes there are some legal assets of a supra-individual nature and, with it, some injured parties. On the contrary, it is proposed that the ideal procedural mechanism for the defense of these supra-individual legal rights resides in collective actions, which should receive the treatment of a particular collective action understood as the exercise of criminal action by legal persons or groups in defense of collective and diffuse interests. Secondly, the problems of penitentiary execution inherent to restorative justice in the field of socio-economic crimes are analyzed.